Cross-border Slovak-Ukrainian cooperation at the time of crisis - Peter Plenta (University of Warsaw, Centre of Migration Research (CMR), 2016)
The events in Ukraine were an impulse for Slovak foreign policy, media, and non-governmental organisations to focus their attention on the eastern neighbour. There was hope that the crises in Ukraine would intensify cross-border cooperation between both countries, especially after pressure from the non-governmental sector. One of the reasons for focusing more attention on Ukraine was a potential threat for Slovakia in terms of the increasing amount of illegal migration and asylum-seeking as a consequence of the military conflict. Despite the modest growth in immigration, the numbers of migrants remain small. On the other hand, bilateral relations between Slovakia and Ukraine faced obstacles regarding energy security issues and so-called "big reverse flow" of natural gas. Regardless of the declared support for the intensification of mutual relations and cross-border cooperation, just a few things have changed. Because of decreasing media interest in the situation in Ukraine, there is also a threat that future (cross-border) cooperation projects will encounter trouble with securing support and financing. However, the visa-free regime for Ukrainian citizens may be a turning point, boosting regional collaboration and changes in migration patterns.
Keywords: 330; Slovakia; Ukraine; cross-border cooperation; visa regime; migration